Construire la catégorie de discipline scolaire en didactique(s) - Reuter, Yves (Linguarum Arena, 2014)
In this paper we examine how the didactics construct theoretically the concept of “disciplinary subject”. We disclose its importance, that is to say we exhibit the epistemological, historical and institutional reasons that explain the links between didactics and subjects. Next, we put forward some explanations to the lost of time that has affected this concept’s theoretical construct. Then we list the chosen categories: definition, descriptive features, “main core”, “disciplinary configuration”, disciplinary system and means of appropriation (through the concepts of “disciplinary awareness” and “disciplinary experience”). To conclude, we consider four questions: the one of some unresolved questions in which the construction of the disciplinary subject conceptualization is involved, the one of the multiplicity of the names of the disciplinary subjects, the one of the critical relationship with these subjects and the one of the links between didactics and compared didactics.